Policy translation and configuration using dynamic template - Yunchuan GUO; Ling LI; Yongjun LI; Lin CHENG; Jun DU; Lingcui ZHANG (Tongxin xuebao)
To solve the problem of complex,cumbersome and error-prone configuration of security devices caused by the heterogeneous configuration modes in complex networks,a dynamic template-based scheme for translating and configuring policy was proposed.In detail,considering the code’s features,the code-based template for translating policies was constructed to configure the command line conversion,and the keyword comparison method was used to ensure the accuracy of policy configuration.Experiments show that the scalability and the accuracy of the proposed scheme.